On Optimization of RIS-Assisted Secure UAV-NOMA Communications with Finite Blocklength - D. Zhao; L. Hu; W. Xiong; H. Cai; Y. Qian; Y. Xing (Radioengineering)
The combination of reconfigurable intelligent surface (RIS) with the unmanned aerial vehicle (UAV) and the non-orthogonal multiple access (NOMA) has emerged as a promising technology in the sixth generation (6G) network. However, UAV downlinks are susceptible to potential eavesdropping attacks due to the open and broadcasting nature of wireless channels. In addition, transmitting information with infinite blocklength (IBL) is impractical in 6G applications. In this paper, we propose a secure RIS-assisted UAV communication system based on NOMA with finite blocklength (FBL) transmission. To maximize the average secrecy rate for all ground users under the mobility and power constraints of the UAV, we jointly optimize the phase shift of the RIS, the trajectory, the transmit power of the UAV, and the user scheduling. To solve the formulated non-convex problem, we first transform the optimization problem into four convex sub-problems, i.e., phase shift optimization, trajectory optimization, transmit power optimization, and user scheduling optimization. Then, an iterative algorithm is developed based on the successive convex approximation (SCA) to solve the four sub-problems. Numerical results show that the average secrecy rate for all ground users achieved with the proposed algorithm is higher than that achieved with the traditional algorithms.